2018
DOI: 10.1016/j.heliyon.2018.e01065
|View full text |Cite
|
Sign up to set email alerts
|

Over-expressed, N-terminally truncated BRAF is detected in the nucleus of cells with nuclear phosphorylated MEK and ERK

Abstract: BRAF is a cytoplasmic protein kinase, which activates the MEK-ERK signalling pathway. Deregulation of the pathway is associated with the presence of BRAF mutations in human cancer, the most common being V600EBRAF, although structural rearrangements, which remove N-terminal regulatory sequences, have also been reported. RAF-MEK-ERK signalling is normally thought to occur in the cytoplasm of the cell. However, in an investigation of BRAF localisation using fluorescence microscopy combined with subcellular fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…In the first study, an exogenous truncated BRAF transfected in NIH3T3 cells was used, and this artificial system cannot be generalized or applied to the endogenous BRAF. In the second study, Shin et al used a non-cancer C2C12 myoblast cell line and found a very tiny fraction of WT BRAF in the nucleus compared to a strong nuclear presence of BRAF V600E [ 34 , 35 ]. Our hypothesis is that WT BRAF activation requires external growth factors, and its localization is totally cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, an exogenous truncated BRAF transfected in NIH3T3 cells was used, and this artificial system cannot be generalized or applied to the endogenous BRAF. In the second study, Shin et al used a non-cancer C2C12 myoblast cell line and found a very tiny fraction of WT BRAF in the nucleus compared to a strong nuclear presence of BRAF V600E [ 34 , 35 ]. Our hypothesis is that WT BRAF activation requires external growth factors, and its localization is totally cytoplasmic.…”
Section: Discussionmentioning
confidence: 99%